Flexing Charity on Social Media: A Thematic Qur'anic Study of Philanthropic Verses - Riska Nur Hidayati; Musholli Musholli (STAI Syaichona Moh. Cholil Bangkalan, 2026)
The rapid development of social media has transformed philanthropy into highly visible digital self-presentation, giving rise to